Development of Indicators of Abuse of Statements (Misbruik Van Omstandigheden) in Indonesia - Khalid, Afif (PT. Anagata Sembagi Education, 2025)
This article explores the development of the doctrine of abuse of circumstances (misbruik van omstandigheden) within Indonesian contract law, primarily shaped through judicial decisions rather than explicit statutory regulation. The doctrine serves as a critical mechanism to assess the validity of agreements and prevent injustices arising from one party exploiting unfavorable situations during contractual formation. The study delves into various scholarly perspectives surrounding abuse of circumstances as grounds for contract cancellation, emphasizing three key aspects: the positional relationship of the parties at the time of contract formation, the fairness and formulation of the agreement, and the moral implications involved. Despite its recognized importance, the absence of clear legal provisions creates challenges in consistently identifying and adjudicating such abuses. The article argues for necessary reforms within the Indonesian Civil Code to codify specific indicators and criteria that can reliably distinguish cases of abuse, thereby enhancing legal certainty and fairness. Ultimately, the research underscores the urgent need for strict and clear regulatory frameworks to minimize divergent interpretations that could undermine justice and contractual security in Indonesia's evolving civil law landscape.